2021
DOI: 10.5114/aoms.2019.89677
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger of the cerebellum 5 promotes colorectal cancer cell proliferation and cell cycle progression through enhanced CDK1/CDC25c signaling

Abstract: Introduction: Colorectal cancer (CRC), mostly caused by external or environmental factors, is the third most common and lethal cancer worldwide. Although a large number of investigations have been carried out to reveal the evolution of CRC, the underlying mechanisms of CRC remain unclear. Material and methods: Expression of zinc finger of the cerebellum 5 (ZIC5) in CRC tissues and cell models was measured by qRT-PCR and IHC. Cell transfection was carried out for ZIC5 overexpression or knockdown. The MTT assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Notably, knockdown of ZIC5 inhibited non-small cell lung cancer cell proliferation and led to cell cycle arrest in G2 phase (16). Another study confirmed that ZIC5 expression was significantly increased in Chinese patients with colorectal cancer, and ZIC5 increased the proportion of cells in S phase to accelerate colorectal cancer cell proliferation (25). Knockdown of ZIC5 in colorectal cancer cells increased glycolytic status and tolerance to low-glucose conditions (26).…”
Section: Discussionmentioning
confidence: 88%
“…Notably, knockdown of ZIC5 inhibited non-small cell lung cancer cell proliferation and led to cell cycle arrest in G2 phase (16). Another study confirmed that ZIC5 expression was significantly increased in Chinese patients with colorectal cancer, and ZIC5 increased the proportion of cells in S phase to accelerate colorectal cancer cell proliferation (25). Knockdown of ZIC5 in colorectal cancer cells increased glycolytic status and tolerance to low-glucose conditions (26).…”
Section: Discussionmentioning
confidence: 88%
“…Zinc finger of the cerebellum 5 (ZIC5) is a transcriptional repressor. It plays an important role in colorectal cancer via regulating cell cycle progression and the modulation of CDC25/CDK/cyclin signaling [ 48 ]. Cystatin SN (cystatin 1, CST1) inhibits cysteine proteases and promotes cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These in vitro results were validated in a mouse model with a smaller tumor size and weight, documented after silencing circ-HIPK3 [ 140 ]. ZIC5 is assiduously involved in promoting carcinogenesis [ 148 , 149 , 150 , 151 ]. Hence, the discovery and characterization of the axis, as mentioned earlier, could be a new way to treat recurrent high-grade glioblastoma.…”
Section: Exosomes As Chemoresistance Mediatorsmentioning
confidence: 99%